Cognitive, Affective and Psycho-Motor Skills in Basic Computer Education Among Intermediate Learners - Zubieto, Aurelio A. (JPAIR Multidisciplinary Research, 2009)
The study determined the level of cognitive, affective and psychomotor skills among selected intermediate pupils in Lucban, Quezon in Basic Computer Education. Particularly, it geared at finding a significant difference in the three levels of learning on Basic Computer Education and probing an E-Material that can be developed to improve the existing status of the selected grade six pupils. The descriptive method utilizing questionnaire as its main instrument limited to determining the three domains of learning Basic Computer Education, characterized the research design. One hundred (100) respondents were randomly selected from chosen public and private elementary schools namely, Casa del Niño Jesus de Lucban (CDNJL), Lucban Adventist Elementary School (LAES), Paaralang Elementarya ng Lucban 1 (PEL 1), and Southern Luzon State University Laboratory Elementary School (SLSU LES). Using weighted mean and chi-square as the statistical measures, results showed that pupils from CDNJL ranked second in cognitive skills, third in the affective and psychomotor skills relevant to computer. Pupils from LAES, however, emerged fourth in the three domains of learning, as contrasted to pupils from PEL 1 who ranked third in the cognitive skills, but first on the affective and psychomotor skills. Meanwhile, SLSU LES pupils garnered first in the cognitive skills, and second on the psychomotor and affective competencies.
Keywords: Cognitive; affective; psychomotor skills; Basic Computer Education